Eastern Influences in Building the Civilization of Morocco Through Ancient Eras: From the Beginnings to Major Achievements - Hamra , Housny; Hamra , Asma (Journal of Ecohumanism, 2025)
The study entitled "Eastern Influences in Building the Civilization of Morocco Through Ancient Eras: From the Beginnings to Major Achievements" provides a comprehensive analytical framework for exploring the complex mechanisms that shaped the civilizational identity of Morocco through interaction with the Eastern heritage. The central research problem stems from questioning the nature of these influences and how to interpret them within the framework of civilizational interaction between the Mashriq (East) and the Maghreb (West), focusing on the qualitative transformations witnessed in the religious, architectural, scientific, and social spheres. The importance of the topic lies in its focus on one of the most prominent phenomena of civilizational interaction in the Islamic world, as it traces the paths of the transfer of ideas, techniques, and customs from the Mashriq to the Maghreb, and how they were absorbed and adapted to the local environment. The approach is distinguished by its analytical depth, which goes beyond traditional historical narration to understand the underlying mechanisms behind the process of acculturation and the assimilation of external influences. The research aims to achieve several key objectives, including analyzing the diverse areas of Eastern influence, understanding the mechanisms of cultural transfer, studying supporting archaeological and historical evidence, in addition to analyzing quantitative and qualitative data related to these influences. It also seeks to determine the extent and value of these influences in shaping the distinctive civilizational features of Morocco. The study adopted a multi-tiered methodology that included the historical method to trace the chronological sequence of events, the analytical method to study texts and archaeological evidence, the statistical method to analyze quantitative data, and the comparative method to highlight similarities and differences with Eastern civilizations. Among the most pivotal terms in the study are: Eastern Influences, Civilizational Interaction, Acculturation, Arabization, Cultural Amalgamation, Civilizational Assimilation. The study reached important results, most notably: Firstly: Eastern influences were a decisive factor in formulating the cultural and religious identity of Morocco, as Islam and its accompanying civilizational framework represented a qualitative leap in the Moroccan civilizational trajectory. Secondly: The study revealed that the interaction process was not one-sided but was characterized by reciprocity, as Morocco was able to add its local touches to the incoming influences, producing a unique civilizational formula. Thirdly: These influences were documented through compelling archaeological and historical evidence, as the analysis of architectural landmarks such as the Al-Qarawiyyin Mosque and the Al-Attarine Madrasa showed a high degree of influence by Eastern models while maintaining local specificity. Fourthly: In the scientific field, the process of knowledge transfer resulted in the establishment of prestigious scientific centers such as the University of Al-Qarawiyyin, which became a beacon of science in the Islamic world, alongside the process of adapting incoming knowledge to suit local needs. Fifthly: On the social level, Eastern migrations, such as those of the Banu Hilal and Banu Sulaym, contributed to enhancing the process of Arabization and entrenching Arab culture, while preserving local components. Finally, the study confirms that the civilizational legacy resulting from this interaction is still alive in contemporary Moroccan culture, making Morocco a successful model of civilizational interaction between the Mashriq and the Maghreb.